The Lives of Chang and Eng : Siam's Twins in Nineteenth-Century America - Orser, Joseph Andrew (Book collections on Project MUSE., 2014)
Connected at the chest by a band of flesh, conjoined twins Chang and Eng Bunker toured the United States and the world from the 1820s to the 1870s, exhibiting their extraordinary bodies as 'freaks of nature' and 'Oriental curiosities'. The brothers constantly professed their normality - they spoke English, attended church, became American citizens, and backed the Confederacy during the Civil War. Yet in life and death, Americans saw the brothers as 'monstrosities', an affront they were unable to escape. This book chronicles the twins' history.